Source of Ore-Forming Fluids and Ore Genesis of the Batailing Au Deposit, Central Jilin Province, Northeast China: Constraints from Fluid Inclusions and H-O-C-S-Pb Isotopes - Li, Haoming; Wang, Keyong; Yan, Xiangjin; Zhao, Qingying; Sun, Lixue (Minerals (Basel), 2024)
The Batailing Au deposit is a vein-type deposit in central Jilin Province, situated in the southern sector of the Lesser Xing’an–Zhangguangcai Range within the eastern Central Asian Orogenic Belt. NE-trending fault-controlled orebodies occur in the Upper Permian Yangjiagou Formation and quartz diorite–porphyrite. The mineralisation process was delineated into three stages: (I) quartz–arsenopyrite–pyrite, (II) quartz–polymetallic sulphides (main Au mineralisation stage), and (III) quartz–pyrite–carbonate. Fluid inclusions (FIs) in quartz were identified as four types: PC-type (pure CO2), C1-type (CO2-bearing), C2-type (CO2-rich), and W-type (aqueous two-phase). Raman spectroscopy analysis revealed that the vapor components of the FIs predominantly comprised CO2 with minor quantities of CH4 in stages I–II. Stages I and II encompassed four types of FIs with homogenisation temperature ranging from 264 to 332 °C and 213 to 292 °C and salinity spanning from 4.7 to 11.2 wt% and 1.8 to 11.6 wt%, respectively. Stage III exclusively contained W-type FIs with homogenisation temperature ranging from 152 to 215 °C and salinity spanning from 1.4 to 6.4 wt%. H-O isotopic values (δD = −84 to −79.6‰, δ18OH2O = 6.2 to 6.4‰ in stage I and δD = −96.4 to −90.4‰, δ18OH2O = 2.8 to 4.4‰ in stage II) and microthermometric data indicated that the ore-forming fluids are initially from a magmatic source, with later meteoric water input. Low C isotopic data from CO2 in FIs in quartz (−24.4 to −24.3‰ in stage I and −23.7 to −22.6‰ in stage II) indicated an organic carbon source. Ore precipitation is mainly attributable to fluid immiscibility. S-Pb isotopic data (δ34S = −3.5 to −1.6‰; 206Pb/204Pb = 18.325–18.362, 207Pb/204Pb = 15.523–5.562, 208Pb/204Pb = 38.064–38.221) revealed that ore metals primarily originated from magma. Based on this research, the origin of the Batailing Au deposit is of the mesothermal magmatic–hydrothermal lode type.